Pemberitaan Akhir Covid 19 Melalui Strategi Komunikasi Humas Pemerintah Kota Surabaya - Lia Qikmatul Maula; Dwi Prasetyo (DIGICOM : Jurnal Komunikasi dan Media, 2023)
The successful management of the pandemic in Surabaya City is a testament to the effective implementation of public communication, which is largely attributed to the Surabaya City Communication and Information Service (Dinkominfo). With the aim of investigating the relationship between the public communication strategy and the reporting on the end of the pandemic in Surabaya City, a study was conducted using descriptive qualitative methods and the theory of issue management analysis by Howard Chase and Barry Jones. The research focused on reportation of the COVID-19 pandemic from January to October 2022 through social media Instagram @sapawarga and the website surabaya.go.id. Findings indicate that the Surabaya City Government prioritizes changing people's behavior and economic recovery over reporting on counterproductive health issues. To monitor issues related to Surabaya City, the government employs conventional, digital, and intelligent media monitors and prioritizes issues based on urgency and alignment with the Surabaya City Government's vision and mission. The formulation of an effective public communication strategy involves determining the target, content, and media strategies, while the implementation of the strategy focuses on the role of the Leader (Mayor) as the main communicator and using the AIDA communication concept to gradually and repeatedly engage the public. The success of public communication is measured by the level of participation from the Surabaya City community in supporting the government's programs and policies.